2018
DOI: 10.1073/pnas.1812025115
|View full text |Cite
|
Sign up to set email alerts
|

Elongation factor P is required to maintain proteome homeostasis at high growth rate

Abstract: Elongation factor P (EF-P) is a universally conserved translation factor that alleviates ribosome pausing at polyproline (PPX) motifs by facilitating peptide bond formation. In the absence of EF-P, PPX peptide bond formation can limit translation rate, leading to pleotropic phenotypes including slowed growth, increased antibiotic sensitivity, and loss of virulence. In this study, we observe that many of these phenotypes are dependent on growth rate. Limiting growth rate suppresses a variety of detrimental phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Because suppressors were directly associated with translation initiation, we first grew cells at 25°C ( Fig. S4G ), which is known to decrease the translation initiation rate ( 45 ), and we found that growth at 25°C decreased both translation initiation and elongation rates. The initiation rate (0.02 sites s −1 ) and elongation rate (6 aa s −1 ) of SRP − cells grown at 25°C were reduced by 1.5 times relative to those of cells grown at 37°C ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because suppressors were directly associated with translation initiation, we first grew cells at 25°C ( Fig. S4G ), which is known to decrease the translation initiation rate ( 45 ), and we found that growth at 25°C decreased both translation initiation and elongation rates. The initiation rate (0.02 sites s −1 ) and elongation rate (6 aa s −1 ) of SRP − cells grown at 25°C were reduced by 1.5 times relative to those of cells grown at 37°C ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To be sure, introducing proline residues in the polypeptide chain slows down translation so much that it becomes difficult or even impossible for runs of proline residues. In the early times of the origin of translation, evolution has selected a specific factor to alleviate this limitation, translation elongation factor EIF5A/EF‐P (Woolstenhulme et al , 2015; Tollerson et al , 2018). Strikingly, this factor is also important for synthesis of a variety of initiator peptides in Bacteria (Aoki et al , 1997; Katoh et al , 2016), implying that the formylation step is a latecomer that has emerged once this essential compensatory process had evolved so as to accommodate proline in polypeptides.…”
Section: The Formylation Of Methionine‐loaded Initiator Trna Its Rolmentioning
confidence: 99%
“…Given this apparent slowdown at proline codons, we examined if genes involved in proline biosynthesis had altered expression levels. However, the three enzymes directly involved in proline biosynthesis -proA, proB, and proC, the proline tRNA ligase -proS, and elongation factor P involved in alleviating ribosome pausing at polyproline motif 40 , were not significantly altered in any of the lines (Fig. S8B).…”
Section: Transcriptional Changes Drive Translational Changesmentioning
confidence: 98%